Da incorporação do proletariado ao direito do trabalho: um estudo sobre o projeto positivista de organização das relações de trabalho no Brasil. - Superti, Eliane (2004)
The present study had as an objective a greater understanding of the problems related to the Social Issue in Brazil. Among the other aspects of this theme, we focus the ideological and political process of elaboration of the positivist project of organization of the work relations, looking for to understand to which extent certain positivist ideals of this project had been incorporated and making up the historical construction of national labor law. Within the set of comtian positivist theory, the ideal of proletariat incorporation into the modern society occupies a core position intrinsically entailed to the political realization of the theory. According to Comte, become the working class integrated part of the capitalist society used to imply realizing the deep moral reform in the political and economic concepts proposed by positivism, reorganizing the society to the extent that turns harmonious the relations between the capital and work. In Brazil, the national positivists claim that the solution for the working issue had such a first challenge overcome the slavery. But the problem could not be solved simply with the abolition, it was necessary a project which integrated the former slavers into the society. Reforming the positivist theory by Augusto Comte from the national needs, the Brazilian positivists made up to the nation a reorganizing project of the working relations, which embraces a large proposal of social reform. Getting a spot in Rio Grande do Sul, such a theory was given an important political expression through Júlio de Castilhos and Borges de Medeiros period of governorship, reaching out the 1907 generation that took part in the revolution of 1930, and led by Getúlio Vargas assumed the pos-revolutionary government. The State configuration from 1930 revealed the assimilation of the positivist ideas of the proletariat incorporation, the social harmony, and the collaboration among the classes. The positivist project if constitutes, thus, in an important source of the ideological inspiration about the working right in Brazil.